Prebiotic Mannan Oligosaccharide Pretreatment Improves Mice Survival Against Lethal Effects of Gamma Radiation by Protecting GI Tract and Hematopoietic Systems - Sanguri, Sweta; Gupta, Damodar (Frontiers in Oncology, 2021)
Total body irradiation (TBI) results in critical injuries in a dose dependent manner that primarily damages highly proliferating tissues including hematopoietic stem cells (HSCs) and intestinal crypt stem cells etc. This may result in hematopoietic syndrome leading to bone marrow failure and gastrointestinal syndrome leading to chronic intestinal functional alterations. Death results from the gastrointestinal syndrome due to sepsis, bleeding, dehydration, and multi-system organ failure. We demonstrate that the prebiotic mannan oligosaccharide (MOS) pretreatment substantially prolongs survival in both male and female mice when administered 2 h prior to radiation either through oral or intraperitoneal route. The radioprotective efficacy of MOS was found to be age dependent and improves survival even in aged mice (12–13 months old). MOS pretreatment effectively abrogates radiation-induced hematopoietic injury and accelerates recovery of lymphocytes and WBCs and alleviates depletion of circulatory blood cells. Results also illustrate that MOS pretreatment abolishes crypt cell death and denudation of villi in comparison to the respective irradiated animals and ameliorates the overall radiation-induced damage to the GI system. MOS pretreatment facilitates intestinal recovery leading to enhanced animal survival demonstrating its protection efficacy against TBI induced mortality. Moreover, MOS pretreated animals show signs of accelerated recovery in terms of severity of radiation sickness symptoms including weight loss and completely abolish TBI associated mortality.